Pemetaan Sebaran Tempat Pembuangan Sampah di Kota Binjai berbasis Sistem Informasi Geografis - Matondang, Muhammad Farouq Ghazali; Damanik, Muhammad Ridha S.; Daulay, Muhammad Reza Fahlepi; Annisa, Shafira Dwi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Abstracts provide a comprehensive overview of research activities that are made briefly. In general, abstracts consist of a maximum of 150 words. Abstract is written in two languages, namely Indonesian and English, typed in 1 paragraph, 1 spaced with Times New Roman font with a font size of 11. The Abstract section contains research points to be investigated such as research objectives, problem solving methods, and research results. which was concluded. Keywords need to be included to describe the area of the problem being studied and the main terms that underlie the implementation of the research. Key words can be single words or combinations of words. Number of keywords 3-5 words. These keywords are required for computerization. Searching for research titles and abstracts is made easier with these keywords